Diverse origin of Plasmodium falciparum in northwest Ecuador - Claudia A. Vera-Arias; L. Enrique Castro; Javier Gómez-Obando; Fabián E. Sáenz (Malaria Journal, 2019)
Abstract Background Ecuador plans to eliminate malaria by 2020, and the country has already seen a decrease in the number of cases from more than 100,000 in 2000 to only 618 in 2015. Around 30% of malaria infections in Ecuador are caused by Plasmodium falciparum. Most malaria population genetics studies performed in Latin America, especially in the Pacific Coast, indicate a high clonality and a clear structure of P. falciparum populations. It was shown that an outbreak of P. falciparum in northwest Ecuador was the result of a clonal expansion of parasites circulating at low levels in the country or re-invading Ecuador from neighbouring territories. However, general characteristics of P. falciparum circulating in the northwest coast of Ecuador have not been determined. The main goal of this study was to genetically characterize the population structure of P. falciparum in coastal Ecuadorian localities bordering with Colombia. Methods Molecular investigation of 41 samples collected from 2013 to 2016 in San Lorenzo County, northwest Ecuador was performed using seven neutral microsatellite markers. Results The genetic population structure of P. falciparum in northwest Ecuador is clearly defined as three different genetic groups previously reported in Ecuador, Peru and Colombia. Conclusions The limited number of P. falciparum clonal types that are circulating in northwest Ecuador, are related to ancestral parasite clonal lineages reported in the Pacific Coast. These parasites could be a product of migration from neighbouring regions or residual clonal types circulating in the country in low proportions. Studies of the genetic characterization of P. falciparum in eliminating areas help determine the possible origin of parasites in order to create strategies to prevent the entrance of new lineages and achieve local elimination of malaria.